Sonochemical degradation of bisphenol A using persulfate activated by hematite nanoparticles - Mahboobeh Dehvari; Farshid Ghanbari; Mehdi Ahmadi (Water Science and Technology, 2021)
In this study, hematite nanoparticles (HNPs) were used as the persulfate (PS) activator for the sonocatalytic degradation of bisphenol A (BPA). The physicochemical properties of the synthesized HNPs were investigated using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). The effect of different operational parameters (pH, nanoparticle dosage, persulfate concentration, and ultrasonic power) on catalytic activity were evaluated. The BPA degradation rate was improved when ultrasonic (US) irradiation was used simultaneously with HNPs for activating PS. According to the results, 98.94% of BPA (10 mg/L) was degraded within 15 min of reaction time at 4 mM persulfate and 0.01 g/L HNPs under ultrasonic irradiation of 250 W. The degree of mineralization of BPA was measured using chemical oxygen demand (COD), and 36.98% was achieved under optimum conditions. Quenching tests were done using different scavenger compounds; these showed that both hydroxyl and sulfate radicals were reactive species in BPA degradation. According to the results of reusability tests, the degradation efficiency decreased to 86.34%, indicating that HNPs can be recycled several times. All of the anions tested, but mainly hydrogen phosphate, had an inhibitory effect on BPA degradation. The results showed that the US/HNPs/PS process is effective for the degradation of the organic pollutants.